Comparison between different breeds of laying hens in terms of eggshell translucency and its distribution in various ends of the eggshell - Han-Da Zhang (Elsevier, 2021)
ABSTRACT: Eggshell translucency is a ubiquitous external eggshell quality problem caused by variations of eggshell ultrastructure or shell membrane. In previous studies, researchers have widely investigated this phenomenon with nutritional, environmental, and genetic perspectives in many breeds. However, most studies referring to phenotypic measurement of shell translucency have been performed using a relatively subjective two-, three-, or four-grading methods, which made it impossible to compare distribution of shell translucency among different breeds. In this study, we aimed to explore variations of translucent eggshell spots in different breeds and their distribution in blunt, middle, and sharp ends of eggshell using a relatively objective grayscale recognition method. We selected 45 eggs from each flock of pure lines, commercial strains, and Chinese local breeds (10 flocks, aged 60 to 70 wk), and stored them in a constant environment for 5 d. Then measured eggshell translucency using grayscale recognition method. Indicators of shell translucency included sum of spot areas on the whole eggshell (SUSA), sum area of the whole eggshell (SUSHA), RSS (ratio of SUSA to SUSHA), quantity of spots (QS), average spot area in eggshell (AAES), and diameter of spots in eggshell (DS). As results, in Hy-Line Brown, Brown-Egg Dwarf Layer, and Taihang (pink-shelled) breeds, phenotypic intensity of eggshell translucency was slight; in Rhode Island Red, Jingfen-1, and Dongxiang breeds, phenotypic intensity of eggshell translucency was relatively extensive; and in Jinghong-1, Hy-Line Sonia, White Leghorn, and Taihang (blue-shelled), phenotypic intensity of eggshell translucency was at an intermediate level. In general, the larger the RSS, the larger the QS, AAES, and DS. Of 3 ends for most breeds, eggshell translucency of blunt and sharp ends was usually greater than that of middle ends, and blunt ends seemed to have the most extensive eggshell translucency. Findings from this study could provide a reference for population selection to locate genes regulating shell translucency and to explore the physical structure mechanism for eggshell translucency formation.